Predictability and Transaction Costs: The Impact on Rebalancing Rules and Behavior - Lynch, Anthony W.; Balduzzi, Pierluigi (Journal of Finance, 2000)
Recent papers show that predictability calibrated to U.S. data has a large effect on the rebalancing behavior of a multiperiod investor. We find that this continues to be true in the presence of realistic transaction costs. In particular, predictability causes the no‐trade region for the risky‐asset holding to become state dependent and, on average, wider and higher. Predictability also motivates the investor to spend considerably more on rebalancing and to rebalance more often. In other results, we find that introducing costly liquidation of the risky asset for consumption lowers the average allocation to the risky asset, though only marginally early in life. Our experiments also vary the nature of the return predictability and introduce return heteroskedasticity.